Vegetation restoration and root morphological features of colonized plants observed at a landscape scar, Matatirtha, Kathmandu, Nepal - Devkota, Bimala Devi; Omura, H; Kubota, T; Paudel, P; Acharya, KP (Banko Janakari, 2008)
In this study, an attempt is made to investigate the vegetation recovery state and morphological features of some colonized plants observed in a four years old landslide scar occurred at Matatirtha, Kathmandu, Nepal. The morphological characteristics of plants like root features, root/shoot ratio, pullout resistive force for individual grass species are investigated. The pullout resistive forces of colonized plants were ranged in between 22-99 Newton. It was revealed that about 30-80% of landslide scare area was covered by naturally grown herbaceous and tree species during four years. The Important Value Index (IVI) of an individual plant was identified to know the relative dominance. The pullout resistive force was influenced by morphological parameters such as shoot height, diameter, length and numbers of roots.Key words: Vegetation recovery; landslide; pullout resistive force; plant morphologyBanko Janakari Vol.16(2) 2006 pp.71-78